Rekonstruksi Tamadun dan Wacana Falsafah Dalam Siri Anime Dr. Stone: Suatu Analisis Epistemologi, Etika, Politik dan Kemanusiaan Dari Perspektif Falsafah Moden dan Pemikiran Islam: Reconstruction of Civilization and Philosophical Discourse in Dr. Anime Series. Stone: An Analysis of Epistemology, Ethics, Politics and Humanity From the Perspective of Modern Philosophy and Islamic Thought - Mohd Azhar, Muhammad Hazim; Muhammad Safwan Harun; Muhammad Ikhlas Rosele (Journal Al-Muqaddimah, 2025)
Analysis of various contemporary discourses can be done through the lens of Islamic thought as an effort to apply the Islamic thought framework in understanding a matter. As an intellectual exercise towards strengthening this discourse, analysis of animation series can be utilized through the Islamic thought approach because anime series from Japan are not just light texts, but contain philosophies that can be pursued. This article examines the Dr. Stone anime series through a philosophical framework that combines modern Western thought and the foundations of Islamic thought with a focus on four dimensions: philosophy of science, philosophy of humanity and the development of civilization, philosophy of moral values ​​and political philosophy. This study uses a qualitative design through thematic content analysis and critical discourse analysis of the Dr. Stone anime series. First, epistemological analysis shows how the character Senku emphasizes truth through scientific experiments and rational prosperity, in line with the Islamic tradition that values ​​knowledge (‘ilm) through reason (‘aql), inductive experiments (tajrībah) and the concept of certainty (yaqīn) in Islamic epistemology. Second, the construction of a new civilization in Dr. Stone reflects the human-nature-technology relationship and can be linked to the maqāṣid al-sharī‘ah thought in Islam which emphasizes maṣlaḥah (goodness) and mizan (balance). Third, the conflict of values ​​between the characters shows the conflict between scientific deontology (moral obligation to explore knowledge) and utilitarianism (maximizing benefits); the Islamic approach emphasizes the obligation to seek knowledge and maqāṣid principles such as the preservation of life, mind and property. Fourth, in the political dimension, the struggle for power based on scientific and physical ideologies involving the characters Senku and Tsukasa is depicted and socio-political negotiations only exist when there is a balance of power and interdependence, in line with the concept of shūrā in Islamic thought. By combining anime narratives with the Islamic thought framework, this article contributes to the discourse of restoring civilization through the integration of knowledge, ethics and power structures, and provides a view of the synergy between modern philosophy and Islamic values ​​in the context of civilization development, indirectly providing a guiding example for the method of analyzing animated series according to the Islamic thought framework.